2023
DOI: 10.1021/acsaem.2c03789
|View full text |Cite
|
Sign up to set email alerts
|

2D MXene-Based Electron Transport Layers for Nonhalogenated Solvent-Processed Stable Organic Solar Cells

Abstract: Implementation of 2D materials is one of the promising routes for improving the efficiency and stability of organic solar cells (OSCs). Due to their tunable optical and electronic properties, MXenes, a family of 2D transition metal carbides and nitrides, have attracted considerable attention and demonstrated their potential for next-generation solar cells. In this work, Ti3C2T x MXene was added into ZnO precursors and applied as a modified composite electron transport layer (ETL) in PM6:N3-based inverted OSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…MXenes have shown potential for use in next-generation solar cells due to their tunability of optical and electrical characteristics. Aryal, Um Kanta, et al 31 created inverted OSCs using the PM6:N3 technology, where the Ti 3 C 2 T x MXene was combined with ZnO precursors and used as a modified composite material for the ETL. Fig.…”
Section: D Mxene-based Etls For Solvent-processed Nonhalogenated Stab...mentioning
confidence: 99%
See 1 more Smart Citation
“…MXenes have shown potential for use in next-generation solar cells due to their tunability of optical and electrical characteristics. Aryal, Um Kanta, et al 31 created inverted OSCs using the PM6:N3 technology, where the Ti 3 C 2 T x MXene was combined with ZnO precursors and used as a modified composite material for the ETL. Fig.…”
Section: D Mxene-based Etls For Solvent-processed Nonhalogenated Stab...mentioning
confidence: 99%
“…It has been proven that solar cells made from the pristine ZnO ETL and PM6:N3 o-xylene can achieve PCE levels of 14.9%. 31 MXene is added to the ZnO ETL (14.1% and 13.7% for addition amounts of 0.5 and 2%, respectively). In the review paper, MXene's function as an ETL and HTL is highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Ti 3 C 2 T x MXene is explored as an active layer, electron/hole transport layer (ETL/HTL), and electrodes in perovskite solar cells, silicon solar cells, , organic/polymer solar cells, , and QD sensitized solar cells (QDSSC) . Recently, Zhang et al fabricated the MXene/GaAs Schottky heterojunction solar cell with an efficiency of 9.6% and excellent stability using a one-step drop casting of MXene dispersion for the first time, as illustrated in Figure b.…”
Section: Optoelectronic Device Applications Of Ti3c2t X Mxenementioning
confidence: 99%
“…39 Recently, Aryal et al demonstrated that 2D Mxene could be embedded with ZnO to reduce this photocatalytic decomposition on ZnO surface. 40 In this work, we investigate the stabilization effect using a naturally occurring antioxidant interlayer between ZnO and active layer.…”
Section: Introductionmentioning
confidence: 99%
“…This, subsequently, leads to charge accumulation and recombination at the ZnO interface, which both strongly reduce the device stability. ,, Various approaches have been explored to control such interfacial degradation: Su and co-workers utilized nitrogen and sulfur-doped graphene oxide nanosheets (NS-GNSs) as a modifier layer for ZnO; Hu et al used aqueous polyethylenimine as a modifier layer; Liu et al developed modified ZnO layers, Me–ZnO, DMSO-ZnO, and sol–gel-ZnO; and Xu et al used C60 self-assembled monolayer (SAM) as a protective buffer layer . Recently, Aryal et al demonstrated that 2D Mxene could be embedded with ZnO to reduce this photocatalytic decomposition on ZnO surface . In this work, we investigate the stabilization effect using a naturally occurring antioxidant interlayer between ZnO and active layer.…”
Section: Introductionmentioning
confidence: 99%